Multiscale structure analysis of a pH-responsive gelatin/hydroxypropyl methylcellulose phthalate blend using small-angle scattering - Kämäräinen, Tero; Nogami, Satoshi; Arima-Osonoi, Hiroshi; Iwase, Hiroki; Uchiyama, Hiromasa; Tozuka, Yuichi; Kadota, Kazunori (Journal of Colloid and Interface Science, 2024)
Hypothesis Hydroxypropyl methylcellulose phthalate (HPMCP) is an enteric polymer that has been employed in drug delivery systems to delay the release of the encapsulated active pharmaceutical ingredients through its pH-responsive solubility change. This has been recently demonstrated as an effective means for delaying the drug release from gelatin/HPMCP hydrogels at gastric pH values. However, structural characteristics of HPMCP agglomeration in gelatin/HPMCP hydrogels is not well understood thus limiting further tailoring of their material properties. Experiments We investigated the multiscale structure of a gelatin/HPMCP hydrogel (1:1 by weight) between pH 2 and 6 at 37 °C, i.e. above the upper critical solution transition temperature of gelatin, using small-angle X-ray scattering and contrast-variation small-angle neutron scattering to understand the pH-responsive structure of HPMCP and the cross-correlation between gelatin and HPMCP. Findings Agglomeration of HPMCP between pH 2 and 4 was evidenced by the formation of mass fractal structures, with a fractal dimension ranging from 1.5 to 2.7, comprising primary particles with a radius of gyration ranging from 70 to 140 Å. Blending with gelatin influenced the fractal structure of HPMCP and the primary particle size. Gelatin and HPMCP exhibited negative cross-correlation in all probed length scales and pH values, which was attributed to volume-exclusion interaction in a double-network-like solution architectur
Keywords: Gelatin; Hydroxypropyl methylcellulose phthalate; Hydrogel; Enteric polymer; Contrast variation; SAXS; SANS